ВТРАТИ ПОТУЖНОСТІ ВІД ВИХРОВИХ СТРУМІВ У РОТОРІ ВИСОКОШВИДКІСНОГО ГЕНЕРАТОРА ЗІ ЗБУДЖЕННЯМ ВІД ПОСТІЙНИХ МАГНІТІВ - Макарчук, О.В. (Інститут електродинаміки НАН України, Київ, 2012)
Design aspects of the high-speed generator with permanent magnet excitation are considered. These aspects are connected with calculation of superficial and pulsating losses in rotor poles. The algorithm of the calculation of a part of these losses conditioned by eddy currents, using FEM-analysis, is given. It is demonstrated an application of this algorithm on example of a 97 kVA generator, 24000 rpm. An influence on the sizes of an active zone on value of these losses, particularly the sizes of the air gap and “opening” slot, is discovered. As it turned out, when a configuration of an active zone of the generator is incorrect, value of such losses can reach a prohibitive amount. It is recommended to apply half-closed slots to decrease these losses on stator. And to make rotor poles segmented, both in axial and in tangential directions. References 7, fіgures 6.